Leptin u zhenshchin, bol'nykh sakharnym diabetom2 tipa, ne poluchayushchikh lekarstvennuyusakharosnizhayushchuyu terapiyu (Ожирение и метаболизм, 2010)
The aim of this study was to investigate the effect of acute hyperinsulinemia to fasting leptin level (fL) secretion and leptin secretion during intravenouse glucose tolerance test (IVGTT). Methods. 32 T2DM women without antidiabetic drugs were studied. Median age of participants was 57,5[50,0;62,5] years, median body mass index (BMI) was 32,7[29,1;37,1]. Glucose intravenouse bolus solution (40%) was dosing (0,75 g/kg BM). Insulin level was investigated in fasting state (FI), 2 min, 70 min and 120 min after glucose loading. Leptin was investigated in fasting (FL) and 120 min after glucose loading. Results. FL level was 21,1[13,6;39,0] ng/ml. Relationships between FL and HOMA-R, аnd between FL and FI were enough strong (r=0,5, р